Growing (with) Muskeg: Oil Sands Reclamation and Healing in Northern Alberta - Joly, Tara (Anthropologica)

(untitled) (University of Victoria, 2021)
Scientists working for oil companies in the Athabasca region are developing methods by which to reclaim muskeg (boreal peatlands) on land disturbed by oil sands extraction. The Alberta government requires companies to reclaim disturbed land by achieving equivalent capability of the landscape to support an end land use. Indigenous community members instead define reclamation as establishing not only quantifiable ecological functions, but also relationships to their traditional territories. Tensions emerge as Indigenous concerns are often subsumed within bureaucratic discourses that favour scientific classification and quantification of land uses in reclaimed areas. Divergent responses to muskeg in reclamation activities are informed in part by these competing emphases on quantifiable landscapes as opposed to those that are relational and growing. This article traces this multiplicity through the examination of government and scientific literature and ethnographic fieldwork with Indigenous communities in northern Alberta. Muskeg is used as an analytical tool to explore competing conceptions of land reclamation. Mistranslation of polysemantic terms like muskeg occur on an ontological level, and settler colonial relations and power imbalances between competing languages and knowledge systems proliferate in reclamation activities.